Comparative Analysis and Immunological Characterization of the Borrelia Bdr Protein Family - Zückert, Wolfram R. (American Society for Microbiology, 1999)
Multiple circular and linear plasmids of Lyme disease and relapsing fever Borrelia spirochetes carry genes for members of the Bdr (Borrelia direct repeat) protein family. To define their common and divergent attributes, we first comprehensively compared the known homologs. Bdr proteins with predicted sizes ranging from 10.7 to 30.6 kDa formed five homology groups, based on variable numbers of short direct repeats in a central domain and diverse N- and C-terminal domains. In a further characterization, Western blots were probed with rabbit antisera raised against either of two purified recombinant Bdr proteins from Borrelia burgdorferi B31. The results showed that antibodies cross-react and several Bdr paralogs 19.5 to 30.5 kDa in size are expressed by cultured strain B31 in a temperature-independent manner. In situ proteolysis, immunofluorescence, and growth inhibition assays indicated that Bdr proteins are not surface exposed. Distinct patterns of cross-reacting proteins of 17.5 to 33 kDa were also detected in other B. burgdorferi, Borrelia garinii, and Borrelia afzelii strains as well as in relapsing fever spirochetes Borrelia hermsii and Borrelia turicatae. Last, we examined whether these proteins are antibody targets during Lyme disease. Analysis of 47 Lyme disease patient sera by immunoblotting and enzyme-linked immunosorbent assays showed that 24 (51%) and 20 (43%), respectively, had detectable antibodies to one or more of the Bdr proteins. Together, these data indicate that Bdr proteins constitute a family of cross-reactive Borrelia proteins which are expressed in the course of Lyme disease and in vitro.